Geriatric Core Competencies for Family Medicine Curriculum and Enhanced Skills: Care of Elderly - Charles, Lesley (Canadian Geriatrics Society, 2014)
BACKGROUND: There is a growing mandate for Family Medicine residency programs to directly assess residents’ clinical competence in Care of the Elderly (COE). The objectives of this paper are to describe the development and implementation of incremental core competencies for Postgraduate Year (PGY)-I Integrated Geriatrics Family Medicine, PGY-II Geriatrics Rotation Family Medicine, and PGY-III Enhanced Skills COE for COE Diploma residents at a Canadian University. METHODS: Iterative expert panel process for the development of the core competencies, with a pre-defined process for implementation of the core competencies. RESULTS: Eighty-five core competencies were selected overall by the Working Group, with 57 core competencies selected for the PGY-I/II Family Medicine residents and an additional 28 selected for the PGY-III COE residents. The core competencies follow the CanMEDS Family Medicine roles. Both sets of core competencies are based on consensus. CONCLUSIONS: Due to demographic changes, it is essential that Family Physicians have the required skills and knowledge to care for the frail elderly. The core competencies described were developed for PGY-I/II Family Medicine residents and PGY-III Enhanced Skills COE, with a focus on the development of geriatric expertise for those patients that would most benefit.